STUDENTS’ PERCEPTION TOWARDS ENGLISH TEACHER PERFORMANCE IN TEACHING ENGLISH AT THE EIGHTH GRADE OF SMPN 6 LUBUK BASUNG - Melisa Agustin Icha; Melyann Melanie; Irwandi Nashir (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
This research is aimed to find out the students’ perception towards English teacher performance in teaching English at the eight grade. Design of this research is survey quantitative research. The instrument of this research is questionnaire. The data was collected from questionnaire to find out the English teacher performance in teaching English based on preliminary activity, core activity, and closing activity. The technique of data analysis in this research is (1) collecting the student’s questionnaire, (2) calculating the percentage of the data, (3) the finding mean of the data, (4) categorizing the perception based on table interpretation. There are five options in answering the questionnaire. Those are strongly agree, agree, neutral, disagree, and strongly disagree. The point of strongly agree is valued 5, meanwhile, the point of agree is valued 4, and 3 point for neutral, 2 point for disagree, and 1 point for strongly disagree. The result showed that the percentage of score students’ perception in teaching performance in preliminary activity aspect is 78,8%. It means that students had perception in good category. Besides, the percentage score of students’ perception in core activity is 76,6% it means that the students had perception in good category. In addition, the third aspect of performance is closing activity, students had perception with score 73,7%, it means the students perception in closing activity was good category. In conclusion, the data above was gotten students had good perception about English teacher performance in teaching English.